Impact of the sensory and postprandial properties of energy drinks on cognition - Mason, C. (2012)
The impact of energy drinks and their ingredients on cognitive functioning has been of considerable scientific interest in recent years; however studies investigating cognitive effects of energy drink consumption have centred on the postprandial impact, that is the influence of their ingredients once absorbed into the blood. It is possible however, that sensory perception of these drinks, or their ingredients can influence cognition.